2013
DOI: 10.1016/j.jnucmat.2013.01.268
|View full text |Cite
|
Sign up to set email alerts
|

Scrape-off layer ion temperature measurements at the divertor target in MAST by retarding field energy analyser

Abstract: Knowledge of the ion temperature (T i ) is of key importance for determining heat fluxes to the divertor and plasma facing components, however data regarding this is limited compared to electron temperature (T e ) data. T i measurements at the divertor target, between edge-localised modes (inter-ELM) H-mode, have been made using a novel retarding field energy analyser (RFEA). Unlike previous L-mode measurements where T i = T e , results from a range of H-mode discharges have shown that at the target T i /T e =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Uncertainty in α LP , given in equation 2, arrises from uncertainty in T i /T e . Previous measurements on MAST have shown that 1 ≤ T i /T e ≤ 2.5 is reasonable for L-mode conditions [26][27][28] .This then gives α LP = 2.7 ± 0.1. Since α BP P cannot be measured directly in the system described in this paper the empirical value of α BP P = 0.6 ± 0.3 6,10,12,14 found across a number of experiments is adopted.…”
Section: Electron Temperature Measurementsmentioning
confidence: 79%
See 1 more Smart Citation
“…Uncertainty in α LP , given in equation 2, arrises from uncertainty in T i /T e . Previous measurements on MAST have shown that 1 ≤ T i /T e ≤ 2.5 is reasonable for L-mode conditions [26][27][28] .This then gives α LP = 2.7 ± 0.1. Since α BP P cannot be measured directly in the system described in this paper the empirical value of α BP P = 0.6 ± 0.3 6,10,12,14 found across a number of experiments is adopted.…”
Section: Electron Temperature Measurementsmentioning
confidence: 79%
“…Figure 6 shows the profile of α LP obtained with this technique in each shot. In these calculations T i = 2T e was assumed, which is motivated by previous measurements on MAST [26][27][28] . Figure 6 shows that the secondary electron emission can have a major impact on the calculation of α LP .…”
Section: Electron Temperature Measurementsmentioning
confidence: 99%
“…Previous measurements made using the SST have shown for an average type III ELM that T i decreases from an initial peak, soon after the ELM occurs, to the previously measured inter-ELM value [20] as a function of time [9]. The measurements here are in an equivalent DN discharge to that in [9] which produces type III ELMs.…”
Section: Sst Measurements Of Type III Elmsmentioning
confidence: 78%
“…Nevertheless, ion temperatures of up to 20 eV are routinely found during ELM events and some measurements of T i ~ 30 eV have also been seen. The highest measured inter-ELM T i in an equivalent plasma was T i = 8 ± 2 eV at ΔR LCFS tgt = 10 cm [20]. By comparing measurements with the IR diagnostic it has been found that it is most likely that a series of filaments have impacted on the target RFEA following an ELM event, any variations of T i during the I sat signal measured at the time of the ELM are likely to be related to filament structures passing the RFEA probe radially due to the timescale of the variations.…”
Section: Discussionmentioning
confidence: 93%
“…It was assumed in previous studies of the SOL width derived from LP data that the ion (T i ) and electron temperatures (T e ) were equal, and this is then used to derive the heat flux to the divertor. Measurements of T i at the divertor have shown that this is not the case [21], especially in the case of low collisionality discharges where there is little coupling between the ions and electrons through collisions. The poor coupling at low density leads to ion temperatures higher than electron temperatures.…”
Section: Regression Of Sol Width To Input Parametersmentioning
confidence: 99%